Analisis Faktor yang Memengaruhi Green Purchase Intention dan Green Customer Behavior (Studi Kasus Pada Produk Tumblr Starbucks) - Tarigan, Nikita Fauziah; Huda, Nurul; Nazwirman, Nazwirman (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2020)
The purpose of this study was to examine the factors of green purchase intention and green customer behaviour by using attitude, subjective norms, behavioral control, and religiosity to use tumblr starbucks on millennials generation. Based on a literature review, this research hypothesis states that attitudes, behavioural control, and religiosity affect green purchase intention. This study uses survey data from questionnaires to 195 respondents. Hypothesis testing techniques are done by using SEM analysis with Smart PLS software. The results of data processing indicate that the Attitude Variable, Behavioural Control, and Religiosity have a significant influence on the green purchase intention to use tumblr of starbucks. Green purchase intention variable has a significant effect on behaviour using electronic money with a t value of 3.152. Religiousity variables and attitude have a greater influence on the green purchase intention to use tumblr than other variables.